Protective Effects of Yinchenhao Decoction on Cholesterol Gallstone in Mice Fed a Lithogenic Diet by Regulating LXR, CYP7A1, CYP7B1, and HMGCR Pathways. (17th September 2018) - Meng, Yong; Meng, Ke; Zhao, Xin; Li, Donghua; Gao, Qiaoying; Wu, Shangwei; Cui, Yunfeng
Abstract : The study attempted to elucidate whether lipid genes are closely associated with lipid metabolic abnormalities during the lithogenic time and how Yinchenhao Decoction (YCHD) works on the transcriptions of lipid genes against cholesterol gallstone model. C57BL/6J mice fed on lithogenic diet (LD) were used for model establishment and randomized into 5 groups. All groups received LD for different weeks with isometrically intragastric administration of YCHD or NS. Biochemical tests were measured and liver tissues were harvested for histological and genetic detection. It was found that all groups with increasing LD showed a following tendency of gallstone incidence, bile cholesterol, phospholipids, total bile acid, and cholesterol saturation index (CSI). Conversely, YCHD could significantly normalize the levels of gallstone incidence, bile lipids, and CSI (CSI<1). As lithogenic time progressed, ABCG5, ABCG8, PPAR- α, and ABCB4 were upregulated, and SREBP2, CYP7A1, and CYP7B1 were downregulated, while CYP7A1, CYP7B1, LXR, and HMGCR mRNA were increased 3-fold under the administration of YCHD. It was concluded that abnormal expressions of the mentioned genes may eventually progress to cholesterol gallstone. CYP7A1, CYP7B1, LXR, and HMGCR mRNA may be efficient targets of YCHD, which may be a preventive drug to reverse liver injury, normalize bile lipids, facilitate gallstone dissolution, and attenuate gallstone formation.